Crédito para agricultura familiar: um estudo no município de São Carlos - Mundo Neto, Martin (2004)
The Brazilian green revolution, started in the 60 s, was based on a pattern that favored large producers and those who could get integrated to rising agri-industrial complexes. In the middle of the 90 s, the creation of PRONAF (National Program for the Strengthening of Family Agriculture) aimed at supporting farmers who had frequently been excluded from agricultural policies, mainly subsidized credit. In spite of the creation of PRONAF and other similar programs, only a small part of family farmers have obtained benefits. Credit access is regarded as essential to family farmers success. Thus, the present work intends to comprehend the obstacles for family farmers to access credit, as well as the alternatives adopted by producers to finance their activities. Theoretical foundation was provided by New Institutional Economics and by studies on family agriculture and rural credit. Empirical data on family farmers in the municipality of Sao Carlos-SP were analyzed from three samples, comprising a total of 132 farmers. Moreover, agents related to rural credit (such as extension service personnel, bank managers, rural union representatives, cooperative members and private companies) were interviewed. Tested hypothesis were separated into two groups. The first is related to obstacles in accessing credit: bank requirements which are not easy to be accomplished by farmers; inappropriate payment conditions; farmers aversion to risks; asymmetry of information (farmers does not know credit options and credit agents does not know the target public); passive attitude by credit agents; and lack of technical assistance. The second group of hypothesis refers to alternatives adopted by farmers: use of complementary income sources, deriving from off-farm activities; and access to informal credit market. Only the hypothesis referring to inappropriate payment conditions was not confirmed. Besides confirming the other hypothesis, empirical data allowed for new findings, such as the incorrect view of family farmers which prevails among local operators of subsidized credit lines. Lack of information is one of the main constraints to credit access. Both farmers and farmers organizations do not know several operational aspects of special credits programs. Also, it was found that farmers suppliers were an important source of credit to family smallholders.